Effect of vaccine diluents on the colonization of Salmonella Typhimurium vaccine in chickens - Siyuan Jia; Andrea R. McWhorter; Samiullah Khan; Nicky-Lee Willson; Daniel M. Andrews; Gregory J. Underwood; Kapil K. Chousalkar (Veterinary and Animal Science)
One of the commonly used methods to control on-farm Salmonella outbreaks in the poultry industry is vaccination. Vaccine diluents may affect vaccine efficacy but there are limited studies on how different diluents affect the colonization of live, attenuated vaccines. In this study, buffered peptone water, Marek's diluent and water were used as the diluents to reconstitute the commercially available Salmonella Typhimurium vaccine (Vaxsafe® ST). The diluent reconstituted vaccine was then given to day-old layer hens to test its effects on gut colonization. The vaccine reconstituted in Marek's diluent and buffered peptone water had a significantly higher colonization rate at 7 days post-vaccination in liver, spleen, oesophagus, crop, and proventriculus. At 14 days post-vaccination, there was a significantly higher vaccine load in the upper digestive tract of chickens that received vaccine reconstituted in Marek's diluent and buffered peptone water. The Marek's diluent and buffered peptone water reconstituted vaccine had a higher detection rate in the chicken's liver and spleen. Colonisation with water as a diluent was higher than the others especially in the lower parts of the intestine at 7 days post-vaccination. There was non-significant variation in the antibody titers at 7- and 14-days post-vaccination. In general, the results demonstrated that the use of nutrient-rich diluents in reconstituting live, attenuated Salmonella vaccine can enhance vaccine colonization. This study establishes a foundation for future work aimed at optimising strategies for vaccine reconstitution, crucial for eliciting a robust immune response in the host.